The Role of Short-Term and Longer Term Immigration Trends on Voting for Populist Radical Right Parties in Europe. Issue 4 (May 2022) - Ramos, Miguel R.; Schumann, Sandy; Hewstone, Miles
The success of populist radical right parties (PRRPs) in Europe has, in part, been attributed to growing immigration, but previous findings have found an inconsistent relationship between immigration and voting for PRRPs. We address previous inconsistencies by suggesting a time-focused perspective on intergroup relations. We disentangle short-term from longer term immigration trends and argue that a recent increase in immigration should predict PRRP support. With time, however, citizens will adapt to these demographic changes and voting for PRRPs could decline. We drew on official immigration records and representative data from the European Social Survey, capturing the voting behavior of 75, 874 individuals from 15 European countries between 2002 and 2014. We found that a recent increase in immigration predicted more PRRP voting, and this relationship was strengthened under conditions of higher economic strain and inequality. In contrast, sustained immigration in the longer term was not related with PRRP votes.